Lived Experience of Special Education Teachers in Quaranteaching - P. Balatucan, Shara Joy; M. Galon, Reinner Andre; Alexandra Alaba, Marion; E. Daño, Precious; E. Gador, Sheena Mae; Cabanilla, Angelito; Cortes, Venus M. (International Journal of Humanities and Education Development (IJHED), 2022)
The closure of schools is one of the most significant impacts of the COVID-19 pandemic. Teaching during the quarantine period presented unique challenges to special education teachers (SPED) who teach students with additional learning needs. This study described the lived experiences of special education teachers while teaching during the quarantine period using the qualitative phenomenology approach. Based on the findings of the study, the success of SPED teachers is defined by active communication and collaboration which help realize the implementation of quarantine teaching and learning. Moreover, four themes emerged for the challenges of SPED teachers, which include: lack of sufficient attention, support and resources from the administration; special education teachers’ technological skills must be improved; special education teachers encountered emotional flounders and uncertainties; and constraints in monitoring and assessing students’ learning and progress. Finally, the coping mechanisms of the SPED teachers are described in two themes: special education teachers adapt practices in the new teaching dynamics and special education teachers develop stress management strategies. Administrators should devise a strategy and distribute adequate funds to meet the needs of the SPED teachers and students in this era of quaranteaching.